2021
DOI: 10.1007/s10098-021-02134-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fe2O3 and Al2O3 nanoparticle-diesel fuel blends on the combustion, performance and emission characteristics of a diesel engine

Abstract: This research investigates the effects of the addition of Fe2O3 and Al2O3 nanoparticles (30, 60, and 90 ppm) and Fe2O3-Al2O3 hybrid nanoparticles to pure diesel fuel on the combustion, performance and emission characteristics of a diesel engine. The results indicated that fuel blends improved the combustion (in-cylinder pressure and heat release rate), performance (power, fuel consumption, and thermal and exergy efficiency), and emission characteristics of the engine. The results showed that the peak combustio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Reason may be the high calorific value and faster flame speed of hydrogen and oxygen buffering effect of nanoparticle which enhanced the combustion process and efficiency. [6,11] Figure 3 demonstrates the CO emission change with engine speed. Incomplete combustion can be the main reason of CO formation.…”
Section: Resultsmentioning
confidence: 99%
“…Reason may be the high calorific value and faster flame speed of hydrogen and oxygen buffering effect of nanoparticle which enhanced the combustion process and efficiency. [6,11] Figure 3 demonstrates the CO emission change with engine speed. Incomplete combustion can be the main reason of CO formation.…”
Section: Resultsmentioning
confidence: 99%
“…It was noticed that spherical shaped iron oxide nanoparticles were obtained and the diameter dispersion ranged from 24 to 65nm. Nouri et al [104] utilized transmission electron microscopy (TEM) and SEM to look at the size and form of nanoparticles, confirming that the size of the nanoparticles was 20-40nm. Shafii et al [102] noticed the size and shape of nanoparticles utilizing TEM examination.…”
Section: Characterization Of Magnetite Nanoparticlesmentioning
confidence: 99%
“…Yuvarajan et al [109] utilized Mahua oil methyl ester (MOME), magnetite nanoparticles, and surfactant in a beaker and stirred with an ultrasonic agitator for 60 min. Nouri et al [104] have used pure diesel with 30, 60, and 90 ppm of magnetite nanoparticles in the solution kept in an ultrasonic bath at a 40-kHz frequency and a temperature of 50°C. The following 2 days, there was some nanoparticle collection.…”
Section: Preparation Of Magnetite Nanofuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ethanol has a high laminar flame propagation velocity, which could significantly improve diesel engine combustion conditions and reduce engine particulate emissions [20]. Some previous studies have also shown that the use of alternative fuels will have a great impact on the combustion performance and exhaust emissions of diesel engines [21,22]. Many regions have adjusted energy policies in the search for clean fuels [23,24].…”
Section: Introductionmentioning
confidence: 99%